Overweight and Cardiac Rhythm Disturbances as Burdening Factors of Forming of Subclinical Systemic Inflammatory Response, Imbalance of Carbohydrate and Lipid Metabolism at Bronchial Asthma in Children - N.N. Kaladze; S.P. Yarovoy (Zaslavsky O.Yu., 2012)
Insulin resistance, metabolic syndrome (in whole), imbalance in «oxidants - antioxidants» system and systemic subclinical inflammation including imbalance of cytokine homoeostasis belong to the main pathogenetic points of contact of bronchial asthma, cardiac rhythm disturbances and overweight. Bronchial asthma, overweight and cardiac rhythm disturbances are the factors of mutual burden of each disease course. It requires the differentiated treatment of mentioned polypathy.